EXPERIMENTAL DETERMINATION OF STABILITY CONSTANTS OF AQUEOUS COMPLEXES - Ohman L.O. (My University, 1998)
Based on the use of thermodynamic data, chemical modelling offers a unique technique to predict and understand the chemistry of metal ions in aquatic systems. This paper discusses the necessary precautions that must be taken to evaluate these thermodynamic data as correctly as possible. The presentation addresses the methodology to be employed in equilibrium studies, emphasizing the need for a continuum between accurate solution preparation, via high quality measurements, to an unbiassed evaluation of the data. The process of extracting a speciation model (i.e., stoichiometric compositions and corresponding equilibrium constants) from potentiometric data is described in some detail. Examples from the authors work with aluminium (III) and silicon (IV) chemistry, conducted at 25° C, are used to illustrate some important aspects. The paper finally advocates the use of graphical representations to visualize the importance of different appearing complexes.
Keywords: AQUATIC CHEMISTRY; EQUILIBRIUM CONSTANTS; THERMODYNAMIC DATA; CONSTANT IONIC MEDIUM METHOD; POTENTIOMETRY; EQUILIBRIUM ANALYSIS; CHEMICAL MODELLING